Eksistensi Hukum Lokal Dalam Pengelolaan Sumberdaya Alam Dan Lingkungan Di Tengah Pusaran Ekonomi Global - Nur Sulistyo Budi Ambarini; Siti Hatikasari (UNIB Press, 2022)
Indonesia is an archipelagic country that has a variety of natural resources that are verypotential as economic resources. These natural resources are found in various regions inIndonesia. The management of natural resources in each region is generally carried outaccording to the local culture in the area concerned. The local rules or laws have basicallybeen in effect for a long time and have been carried out from generation to generation by thelocal community. As is the case in Bengkulu Province which has natural resource potentialwith local culture and rules in managing natural resources. Regarding local law, which wasoriginally a means of managing and utilizing natural resources in the region, at this time,especially in the era of economic globalization, it is not only dealing with state law (nationallaw) but also economic and legal issues in the international context. This paper seeks toexamine the problem of how the existence of local law is related to the use and managementof natural resources in the era of economic globalization. The writing of this article isextracted from several results of legal research that has been carried out using non-doctrinallegal research methods through a socio-legal studies approach. Based on the results ofresearch in several locations in Bengkulu Province, applicable local laws relating to the useand management of natural resources have experienced a shift, although in some areas locallegal values are still believed and become guidelines for local communities. This is becauseapart from the enactment of state (national) law, the enactment of regional autonomy is alsodue to the need for economic development in the global era.